2011
DOI: 10.1007/s11423-010-9184-z
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the artifacts and process of constructing computers games about environmental science in a fifth grade classroom

Abstract: This study employed a case study design (Yin, Case study research, design and methods, 2009) to investigate the processes used by 5th graders to design and develop computer games within the context of their environmental science unit, using the theoretical framework of constructionism. Ten fifth graders designed computer games using Scratch software. The results showed students were able to design functional games, following a learning-by-design process of planning, designing, testing, and sharing. Observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 25 publications
6
78
0
4
Order By: Relevance
“…The study has shown that even within eight hours of lessons children were able to make progress with Scratch and their learning of programming. This was similar to the results of Baytak and Land (2011), who reported that children had completed games after 10 Scratch lessons or 6 for their experienced children, as well as being similar to the game construction work of Robertson and Howells (2008) with the Neverwinter Nights project.…”
Section: -3supporting
confidence: 86%
See 1 more Smart Citation
“…The study has shown that even within eight hours of lessons children were able to make progress with Scratch and their learning of programming. This was similar to the results of Baytak and Land (2011), who reported that children had completed games after 10 Scratch lessons or 6 for their experienced children, as well as being similar to the game construction work of Robertson and Howells (2008) with the Neverwinter Nights project.…”
Section: -3supporting
confidence: 86%
“…Children were given 8 lessons to introduce them to programming and also to gauge how much they enjoyed working with Scratch. Baytak and Land (2011) in their study focused on learning by design where 10 to 11 year old children planned and designed and then created their game with Scratch during a science project. At Harvard University Scratch has been used as an introduction to programming for new undergraduate students (Malan & Leitner, 2007;Malan, 2010).…”
Section: Scratchmentioning
confidence: 99%
“…For these reasons, qualitative and quantitative analysis can be used especially from multiple sources to enhance the trustworthiness of a study. Common assessment tools are observation field notes, audio/video recordings data, deliverables collection, interviews, evaluation forms and rubrics and pre/post surveys so as to evaluate student attitudes, motivation and programming concepts [19][20][21][22][23][24]. Furthermore, there are free available web tools that automatically explore the presence of programming concepts in the students' Scratch files, such as Dr. Scratch [25,26] and Scrape [27].…”
Section: Proposed Game Design and Development Stagesmentioning
confidence: 99%
“…Even though Scratch has been actively used in the scene of education as a creative computing tool, most applications in the literature focus on its effects on computational thinking, science learning, digital literacy, and perception of computer-based majors (e.g., Baytak & Land, 2011;Blau, Zuckerman, & Monroy-Hernandez, 2009;Brennan, 2011;Kafai, Peppler, & Chiu, 2007;Maloney, Peppler, Kafai, Resnick, & Rusk, 2008;Meerbaum-Salant, Armoni, & Ben-Ari, 2010;Wolz, Stone, Pulimood, & Pearson, 2010). Unfortunately, there is limited number of studies focusing on applications of Scratch in mathematics education.…”
Section: Place Of Creative Computing In Learning Mathematicsmentioning
confidence: 99%